2019
DOI: 10.5271/sjweh.3860
|View full text |Cite
|
Sign up to set email alerts
|

Precarious employment in occupational health – an OMEGA-NET working group position paper

Abstract: Despite the growing use of the term precarious employment, there is no consensus on a theoretical framework or definition. This hampers the study of the subject, especially in public and occupational health. We propose a theoretical framework for understanding precarious employment as a multidimensional construct where unfavourable features of employment quality accumulate in the same job. Future research should apply an intersectional and multi-level approach to analysis, with a focus on improving exposure as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
142
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 105 publications
(149 citation statements)
references
References 35 publications
0
142
0
7
Order By: Relevance
“…Finally, several rounds of discussions were held among the authors to reach consensus on which subtheme should be designated to which theme and how these themes should be clustered into what we will henceforth call dimensions of PE. Inclusion or exclusion of the dimensions was then guided and based on a theoretical framework for PE developed by Bodin et al (16).…”
Section: Qualitative Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, several rounds of discussions were held among the authors to reach consensus on which subtheme should be designated to which theme and how these themes should be clustered into what we will henceforth call dimensions of PE. Inclusion or exclusion of the dimensions was then guided and based on a theoretical framework for PE developed by Bodin et al (16).…”
Section: Qualitative Analysismentioning
confidence: 99%
“…We anticipated that our thematic approach could generate dimensions that would fall outside the common understanding of PE and decided, a priori, to apply a theoretical framework to guide our analysis in the exclusion of such dimensions. The aim of the framework is to understand PE as a multidimensional construct where unfavorable features of employment quality accumulate in the same job (16). This framework builds on previous work by several leading researchers in this field (6,12,13,(85)(86)(87), and locates PE at the level of employment relationships to include salary, working times, contractual relationship and rights.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Precarious employment (PE) is recognized as a multidimensional construct encompassing several aspects of employment conditions, including lack of protective regulation, short/uncertain employment duration, lack of fringe benefits and poor wages (1)(2)(3)(4)(5)(6)). Yet, no internationally accepted definition transcending historical and socio-political contexts currently exists (5,6). In addition, unidimensional measures such as type of employment [eg, (7)(8)(9)] are still widely applied to operationalize PE in epidemiological research.…”
mentioning
confidence: 99%
“…Similarly, one investigation of the effect of precarious employment on SA in four Nordic countries showed that precarious employment was associated with SA of 7 days or more, and another report on health-related outcomes (including long-term SA) in 28 countries in Europe cited an association with SA of more than 15 days [37,38]. In both studies, however, the authors measured precarious employment as a multidimensional construct based on indicators obtained from several dimensions (e.g., employment instability, lack of power and rights, reduced salary), which captured the accumulation of unfavourable aspects of employment quality [39]. Therefore, the results derived from these studies may not be directly comparable to the current ndings from our analyses of LMP patterns based on employment status mobility across different stages of the working life course.…”
Section: Discussionmentioning
confidence: 99%